Sexual Dimorphism of Maxillary Sinus: A Morphometric Analysis using Computed Tomography - Kandel, Santosh; Shrestha, Raju; Sharma, Rupesh; Sah, Sanjay Kumar (Journal of Lumbini Medical College, 2020)
Introduction: Gender determination is the important aspect of forensic science. Most of the bones used for sex determination are badly disfigured and found in incomplete state, thus bones recovered intact are used. Maxillary sinus being recovered intact can be used for gender determination by measuring maxillary sinus dimension through computed tomography (CT). The aim of this study was to assess sexual dimorphism using morphometric maxillary sinus measurements through CT scan. Methods: This analytical cross-sectional study included CT scan images of 80 patients (40 males and 40 females). Maxillary sinus mediolateral (ML), superoinferior (SI), anteroposterior (AP) linear dimensions and volume were measured. All the measured parameters were then subjected to Student’s t-test to determine mean difference between males and females and discriminative statistical analysis to determine gender. Results: The mean value of maxillary sinus length, width, height and volume in males on both right and left sides were (3.80±0.175, 3.74±0.209) cm, (2.57±0.317, 2.51±0.295) cm, (3.55±0.338, 3.5±0.286) cm and (17.49±3.909, 16.54±3.274) cm3 respectively and in females (3.67±0.250, 3.64±0.256) cm, (2.37±0.297, 2.34±0.3222) cm, (3.29±0.280, 3.23±0.254) cm and (14.42±2.935, 13.81±2.779) cm3 respectively. The discriminative analysis showed that the accuracy of maxillary sinus measurements was 72.5% in females and 75% of males (overall accuracy = 73.8%). Conclusion: The maxillary sinus measurements are valuable guide for sex determination with relatively good accuracy rate.